PEMANFAATAN SARI BUAH PEPAYA (Carica papaya L.) UNTUK PENINGKATAN VITALITAS PASCALARVA UDANG VANAME (Litopenaeus Vannamei) SELAMA MASA ADAPTASI PENURUNAN SALINITAS - Ferdinand Hukama Taqwa; Marsi .; Adias Praja (Universitas Sriwijaya, 2014)
ABSTRACT The purposes of this research were to increase vitality of white shrimp postlarvae during adaptation time to salinity decrease with the addition of papaya juice, and to assess the physical and chemical properties of water during their adaptation. The research was conducted in October 2011 at the Laboratory of Aquaculture, Aquaculture Study Program, Faculty of Agriculture, Sriwijaya University.Â The research used a completely randomized design in order to evaluate the effect of a various papaya juice concentration. The concentrations used were without papaya juice addition (P0), addition of papaya juice equivalent to 15 ppm K+ (P1), addition of papaya juice equivalent to 30 ppm K+ (P2), addition of papaya juice equivalent to 45 ppm K+ (P3), and addition of papaya juice equivalent to 60 ppm K+ (P4). Each treatment was repeated 3 times. The results of this current study showed that the addition of papaya juice equivalent to 15 ppm (P1) in media that used to decrease salinity was concluded as the best treatment, and gave the survival rate of 65.56%, glucose level of 156.67 mg.dL-1 and oxygen consumption rate of 4.807 mg O2.g-1.hour-1. The physicsal and chemical properties of media used for adaptation were still within a tolerable range for white shrimp postlarvae, except pH tent to be lower than the criteria. Â Keywords : vitality, papaya, white shrimp, adaptation, salinity